MODEL PENYUSUNAN BAHAN AJAR MEMBACA BERBASIS PENDIDIKAN MULTIKULTURAL DAN E-LEARNING - Endah Priyatni (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to develop a guide model for reading materials development based on multicultural education and e-learning. It employed a research and development design with Recursive, Reflective Design and Development. It successfully developed a guide model for reading materials development based on multicultural education which was in the form of an e-learning package. The guide contains a set of rules and steps that teachers should understand and carry out in preparing and developing reading materials based on multicultural education and e-learning. The guide is in the form of an interactive CD and booklet. It has been tried out to product users and validated by experts and practitioners.